Frequency Of Scabies With Relation To Season In Patients Attending The Outdoor Patient Department Of A Tertiary Care Hospital - Alam, Shaista; Khan, Humaira; Orakzai, Shabir Ahmed; Ahmad, Rafiq; Ullah, Mohib; Naveed, Mian Muhammad (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Background: Scabies is a frequently diagnosed condition at hospitals worldwide, particularly in the developing world. It is the commonest cause of intense itching of skin. Methodology: This descriptive cross-sectional study was conducted at the outpatient department of Ayub Teaching Hospital, from Jan 2012 to Dec 2014. Data of the patients attending the OPDs was collected and grouped month- and season-wise for each year. The descriptive data was presented as tables and graphs. Results: We found that the frequency of scabies increased over the period of study i.e. 3.8% in 2012 to 4.23% in 2014.The winter season has highest frequency of scabies (28%) as compared to other seasons. Conclusion: Scabies is a contagious disease and spreads by proximity, therefore its incidence increases in winter. Keywords: Scabies, Winter, Itching, Poverty, Contagious.